Low cost 3D foot scan with Kinect. (2018) - Zhao, Kaiwei; Luximon, Ameersing; Chan, C.K.
Accurate 3D digital foot model is extremely useful in shoe or orthotics design and other medical situations such as podiatric therapy. In view of the fact that most of the 3D data-acquisition devices on the market are either expensive though high accuracy (e.g., high-end laser scanner), or with poor maneuverability and efficiency (e.g., image-based stereography), or deficient portability (e.g., large-size scanning machine or types requiring support frame), we propose a new method for human foot scanning in this paper. Microsoft Kinect sensor was adopted as the key device in this approach and proved a smart and efficient scanner in 3D foot data acquisition according to a detailed comparison with other scanners in terms of scan time, cost, operability and portability. Accuracy check of the sphere and foot scanning results also demonstrates decent precision of the proposed scanning system.